PENGUATAN QUADRICEPS MENGGUNAKAN METODE CLOSED KINETIC CHAIN LEBIH MENJAGA SUDUT QUADRICEPS (Q ANGLE) DIBANDING DENGAN OPEN KINETIC CHAIN PADA SUBJEK DENGAN ABNORMAL SUDUT QUADRICEPS - Romadhon, Aditya Johan; Adiatmika, I Putu Gede; Imron, Muh. Ali; Weta, Wayan; Ayu Inten Dwi Primayanti, I Dewa; Munawwarah, Muthiah (Sport and Fitness Journal, 2017)
Introduction: Quadriceps strengthening usualy find in fitness center or clinical rehabilitation physiotherapy programs, there are two methods in strengthening quadriceps programs, closed kinetic chain and open kinetic chain methods, several researchers use to used these methods for reducing pain intensity, improve functional ability and reducing quadriceps angle, indeed these methods can be used to prevent patellofemoral pain syndrome risk in asymptomatic person with abnormal q angle. Purpose: Purpose of this study is to study the difference of closed and open kinetic chain to maintain quadriceps angle on subject with abnormal quadriceps angle. Method: This experimental study is to compare closed and open kinetic chain to maintain quadriceps angle in subject with abnormal quadriceps angle, thirty six males samples 15 to 21 years old devided into two Groups, Group 1 applied a treatment with closed kinetic chain methods using barbell squat training and the second group have applied a treatment with open kinetic chain method using leg extension training, quadriceps angle measured before and after treatment to each Group, Result: Both quadriceps strengthening methods, closed and open kinetic chain has same beneficial to maintain quadriceps angle, Group 1 after analyzed by paired t test show the mean right quadriceps angle 13.38 ± 2.93 degree and the mean of left quadriceps angle 12.88 ± 2.44 degree, with significancy value p = 0.001, likewise in Group 2 after analyzed by paired t test show the mean of right quadriceps angle 15.66 ± 2.74 degree and the mean of left quadriceps angle is 15.38 ± 3.22 degree, with significancy value p = 0.001, but closed kinetic chain method is more effective than open kinetic chain in maintaining quadriceps angle with p < 0.05. Conclusion: Therefore this result of study can be reference for reader as an athlete, fitness instructor and physiotherapist in order to get better understanding to choose and create best training program for quadriceps strengthening. Therefore it’s been suggest to someone if they have abnormal quadriceps angle, they must choose the closed kinetic chain exercise as the main program in quadriceps training program